2017
DOI: 10.1177/0022034516685071
|View full text |Cite
|
Sign up to set email alerts
|

Secretable Small RNAs via Outer Membrane Vesicles in Periodontal Pathogens

Abstract: MicroRNAs (miRNAs) have been shown to be major regulators of eukaryotic gene expression. However, bacterial RNAs comparable in size to eukaryotic miRNAs (18-22 nucleotides) have received little attention. Recently, a novel class of small RNAs similar in size to miRNAs (miRNA-size, small RNAs or msRNAs) have also been found in several bacteria. Like miRNAs, msRNAs are approximately 15 to 25 nucleotides in length, and their precursors are predicted to form a hairpin loop secondary structure. Here, we identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
181
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(194 citation statements)
references
References 39 publications
4
181
1
Order By: Relevance
“…91,92 Recently, we and other colleagues found that msRNAs in OMVs of pathogenic bacteria can be delivered into host cells and thereby modulate host immune responses. 93,94 msRNA in P. aeruginosa reduced interleukin-8 (IL-8)…”
Section: Evs and Small Rna Secretionmentioning
confidence: 99%
“…91,92 Recently, we and other colleagues found that msRNAs in OMVs of pathogenic bacteria can be delivered into host cells and thereby modulate host immune responses. 93,94 msRNA in P. aeruginosa reduced interleukin-8 (IL-8)…”
Section: Evs and Small Rna Secretionmentioning
confidence: 99%
“…Interestingly, OMVs contain a wide range of RNAs including ribosomal RNA (rRNA), transfer RNA (tRNA), messenger RNA (mRNA), and small non-coding RNA (sRNA) (Ghosal et al, 2015; Ho et al, 2015; Sjöström et al, 2015; Blenkiron et al, 2016; Choi et al, 2017; Soares et al, 2017; Dauros-Singorenko et al, 2018), which indicates that OMVs are important to study in the context of extracellular RNA communication.…”
Section: Introductionmentioning
confidence: 99%
“…This 23-nt small RNA molecule, named MM-H, is derived from a precursor stem-loop structure, requires the mammalian host cell RNA processing machinery for its biogenesis, and probably also affects the expression of the eukaryotic host, rather than bacterial genes [21]. Small RNAs comparable in size to eukaryotic microRNAs have also been identified in periodontal pathogens such as: leukotoxin LtxA—producing Aggregatibacter actinomycetemcomitans ; engaged in the production of the haemolytic toxin Porphyromonas gingivalis strain; responsible for production of highly toxic metabolites Treponema denticola bacteria [22] and a key player in the colonization of the human oral cavity Streptococcus sanguinis [49]. It was observed that the identified microRNA-size RNAs are secreted from the periodontal pathogens via bacterial outer membrane vesicles (OMVs) and affect the eukaryotic host immune system by suppressing the expression of certain cytokines [22].…”
Section: Something Smaller Than Srnas—true Micrornas In Prokaryotimentioning
confidence: 99%
“…Small RNAs comparable in size to eukaryotic microRNAs have also been identified in periodontal pathogens such as: leukotoxin LtxA—producing Aggregatibacter actinomycetemcomitans ; engaged in the production of the haemolytic toxin Porphyromonas gingivalis strain; responsible for production of highly toxic metabolites Treponema denticola bacteria [22] and a key player in the colonization of the human oral cavity Streptococcus sanguinis [49]. It was observed that the identified microRNA-size RNAs are secreted from the periodontal pathogens via bacterial outer membrane vesicles (OMVs) and affect the eukaryotic host immune system by suppressing the expression of certain cytokines [22]. Interestingly, OMVs serve as secretory vehicles by which pathogens not only modulate the host immune response, but also deliver toxins into host cells and are, thus, considered as a potent virulence mechanism [50].…”
Section: Something Smaller Than Srnas—true Micrornas In Prokaryotimentioning
confidence: 99%
See 1 more Smart Citation